Impact of tricuspid regurgitation on postoperative outcomes after non-cardiac surgeries. Issue 1 (21st April 2020) - Parikh, Parth; Banerjee, Kinjal; Ali, Ambreen; Anumandla, Anil; Patel, Aditi; Jobanputra, Yash; Menon, Venu; Griffin, Brian; Tuzcu, E Murat; Kapadia, Samir
Abstract : Objective: Tricuspid regurgitation (TR) severity has known adverse implications, its impact on patients undergoing non-cardiac surgery (NCS) remains unclear. We sought to determine the impact of TR on patient outcomes after NCS. Methods: We performed a retrospective cohort study in patients undergoing NCS. Outcomes in patients with moderate or severe TR were compared with no/trivial TR after adjusting for baseline characteristics and revised cardiac risk index (RCRI). The primary outcome was defined as 30-day mortality and heart failure (HF), while the secondary outcome was long-term mortality. Results: Of the 7064 patients included, 312 and 80 patients had moderate and severe TR, respectively. Thirty-day mortality was higher in moderate TR (adjusted OR 2.44, 95% CI 1.25 to 4.76) and severe TR (OR 2.85, 95% CI 1.04 to 7.79) compared with no/trivial TR. There was no difference in 30-day HF in patients with moderate TR (OR 1.48, 95% CI 0.90 to 2.44) or severe TR (OR 1.42, 95% CI 0.60 to 3.39). The adjusted HR for long-term mortality in moderate TR was 1.55 (95% CI 1.31 to 1.82) and 1.87 (95% CI 1.40 to 2.50) for severe TR compared with no/trivial TR. Conclusion: Increasing TR severity has higher postoperative 30-day mortality in patients undergoing NCS, independent of RCRI risk factors, ejection fraction or mitral regurgitation. Severity of TR should be considered in risk stratification for patients undergoing NCS.